Implementasi Pendidikan Karakter dalam Pendidikan Agama Islam Berwawasan Multikultural di SDN 27 Bengkulu Selatan - Agung Wahyudi (GHAITSA : Islamic Education Journal, 2024)
Character education and evaluation of multicultural learning in elementary schools (SD) adjusted with the level of thinking of children in elementary school. Where is still in the beginning abstract stages. Character education is a system of character cultivation to the school community which includes knowledge, awareness or willingness, and actions to carry out these values, both from God Almighty (Almighty), ourselves, other people, the environment, and the nation so that humans become perfect humans. In fact, multicultural education is indeed an integral part at all levels education. Therefore, the cultivation of multicultural values should ideally be applied in all subjects in formal education.